Lack of de novo Phosphatidylinositol Synthesis Leads to Endoplasmic Reticulum Stress and Hepatic Steatosis in cdipt-Deficient Zebrafish - Thakur, Prakash C (2011)
Hepatic steatosis is the initial stage of non-alcoholic fatty liver disease (NAFLD) and may predispose to more severe hepatic disease, including hepatocellular carcinoma. Endoplasmic reticulum (ER) stress has been recently implicated as a novel mechanism that may lead to NAFLD, although the genetic factors invoking ER stress are largely unknown. During a screen for liver defects from a zebrafish insertional mutant library, we isolated the mutant cdipt(hi559Tg/+) (hi559). CDIPT is known to play an indispensable role in phosphatidylinositol (PtdIns) synthesis. Here we show that cdipt is expressed in the developing liver and its disruption in hi559 mutants abrogates de novo PtdIns synthesis, resulting in hepatomegaly at 5-dpf. The hi559 hepatocytes display features of NAFLD, including macrovesicular steatosis, ballooning, and necroapoptosis. Gene set enrichment of microarray profiling revealed significant enrichment of ER stress response (ERSR) genes in hi559 mutants. ER stress markers, including atf6, hspa5, calr, xbp1, are selectively upregulated in the mutant liver. The hi559 expression profile showed significant overlap with that of mammalian hepatic ER stress and NAFLD. Ultrastructurally, the hi559 hepatocytes display marked disruption of ER architecture with hallmarks of chronic unresolved ER stress. Induction of ER stress by tunicamycin in wild-type larvae results in a fatty liver similar to hi559, suggesting that ER stress could be a fundamental mechanism contributing to hepatic steatosis. Conclusion: Cdipt-deficient zebrafish exhibit hepatic ER stress and NAFLD pathologies, implicating a novel link between PtdIns, ER stress, and steatosis. The tractability of hi559 mutant provides a valuable tool to dissect ERSR components, their contribution to molecular pathogenesis and evaluation of novel therapeutics of NAFLD.